2021
DOI: 10.1007/s10803-021-05211-5
|View full text |Cite
|
Sign up to set email alerts
|

Child and Parental Mental Health as Correlates of School Non-Attendance and School Refusal in Children on the Autism Spectrum

Abstract: Children on the autism spectrum miss more school than their peers, but limited work has explored why this may be. This study aimed to document the frequency at which children on the autism spectrum miss half and full days of school and the reasons for these absences. Parents of 106 school-aged children on the autism spectrum completed online questionnaires on rates of school non-attendance, family factors, child anxiety, and parental mental health. On average across a four week period, children missed 6 full d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 57 publications
3
35
0
Order By: Relevance
“…Future research should investigate school attendance more closely among children with neurodevelopmental conditions who have a formal recognition of their special educational needs. Of the potential confounders examined in the analyses, older child age and higher level of family socioeconomic deprivation were associated with a higher rate of absence and a higher likelihood of persistent absence, similar to findings from studies before the pandemic (Adams, 2021; Fleming et al, 2020; John et al, 2022; Totsika et al, 2020). Interestingly, supplementary analyses that examined the independent association of autism and intellectual disability indicated the presence of these specific neurodevelopmental conditions were not significantly associated with school absenteeism over and above the effect of home learning location and other study covariates.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Future research should investigate school attendance more closely among children with neurodevelopmental conditions who have a formal recognition of their special educational needs. Of the potential confounders examined in the analyses, older child age and higher level of family socioeconomic deprivation were associated with a higher rate of absence and a higher likelihood of persistent absence, similar to findings from studies before the pandemic (Adams, 2021; Fleming et al, 2020; John et al, 2022; Totsika et al, 2020). Interestingly, supplementary analyses that examined the independent association of autism and intellectual disability indicated the presence of these specific neurodevelopmental conditions were not significantly associated with school absenteeism over and above the effect of home learning location and other study covariates.…”
Section: Discussionsupporting
confidence: 71%
“…We further examined whether learning location was associated with a specific type of absenteeism, namely, school refusal. School refusal is the most prevalent type of absence in autistic children (Adams, 2021; Totsika et al, 2020) and as a type refers to absence accompanied by emotional distress because the child is reluctant to attend (Heyne et al, 2019). Our findings indicated that home learning location was not associated with a higher rate of school refusal later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 school days) had elapsed. In prior studies, the SNACK has been used to measure reasons for school non‐attendance among autistic school students (Adams 2022), autistic students with and without ID (Totsika et al 2020) and students with neurodevelopmental conditions (Totsika et al . 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The condition significantly affects the life of the sufferers, leading them to devastating and long-lasting trauma. Particularly in children and teenagers, the acts were also reported to contribute to the school refusal of the psychological and physical attack (Adams, 2021, Munkhausen et al, 2019. Therefore, a study on people with ASD is significant in dealing with the problem.…”
Section: Introductionmentioning
confidence: 99%